Fermented beverages among indigenous Latin American societies - Lasso García, Christian; German Bermúdez, Fátima Andrea; Vanden Berghe, Wim; Gabriela Zurita-Benavides, María; Orellana-Manzano, Andrea (Frontiers in Sustainable Food Systems, 2024)
Traditional fermented beverages are a valuable cultural, economic and social heritage of Latin American societies that deserve to be preserved and strengthened within the framework of sustainable development and respect for diversity. Therefore, this article will demonstrate, through scientific literature, the importance-value for indigenous societies and the nutritional contributions of the most traditional beverages of North and South America.This systematic review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) verification protocol. The study focused on explores the nutritional information of South and Central American fermented beverages. The search was conducted in the Biomed, PubMed, ScienceDirect, Scopus, Scielo and Google Scholar databases to identify publications published within the past 15 years. However, the presence of toxic compounds such as biogenic amines and phenols that affect the quality of the product and human health has been detected. In addition, it was found that macro- and micronutrients, vitamins, and microorganism differ according to the type of raw material used. It was concluded that corn is the most widely used raw material to produce fermented beverages in Latin America. At the same time, Mexico has more research on this product, and most analysis is being carried out on the use of corn in the production of fermented beverages. In addition, several studies have shown that the use of validated and standardized methodologies for the detection of biogenic weapons is crucial to ensure accurate identification, effective response and compliance with legal and security requirements in this critical area.